Les bois de construction du boulevard Dr Henri-Henrot à Reims/Durocortorum - Willy Tegel (Gallia)
By virtue of being located partially within the former river bed of the Vesle’s right bank, as well as its being situated closely to the water table, the excavation, in Reims, of the boulevard Dr. Henri-Henrot provided an excellent quality of preservation for perishable materials, including construction wood dating back to Antiquity. The material culture includes piles, planks, beams and staves, that were used in wall foundations, riverbank development, quays, dikes and formwork for gutters, basins, wells or pits. Few Gallo-Roman sites north of the Alps have yielded such large quantities of wooden remains and, even fewer presenting such an excellent a state of preservation. The method used here, known as dendrochronology, allows for the precise dating of wooden remains by examining the tree-rings. Seeking answers to chronological questions form the basis of this analysis, which seeks the comparison of the information collected with archaeological hypotheses. Of the 1,192 timbers collected and analyzed in context, 301 timber remains from 41 structures were dated. The dates obtained provide anchor points for the occupation history of the southern periphery of the ancient city of Reims. The first building was established around 13 BC and the last in 307 AD. During the first two centuries of our era, continuous building activity in this area was revealed through dendrochronological analysis. The 3rd c., however, demonstrated more punctual activity and only toward the beginning of the 4th c. did these activities resume with their prior intensity. The exceptional number of wooden elements recovered on site not only provides information on the state of the forest at that time, but also on its management, both of which may be related to changing environmental conditions and socio-economic processes. Furthermore, the wooden constructions, the applied techniques, as well as the extremely complex wooden assemblages documented through this approach provide an excellent account of carpentry and woodworking techniques in use during the Roman period. Thus, this study also provides a relevant and significant contribution to the history of these techniques.